3-hydroxy butyrate dehydrogenase 2 deficiency aggravates systemic lupus erythematosus progression in a mouse model by promoting CD40 ligand demethylation. Issue 2 (1st February 2022) - Yang, Bo; Hou, Shihao; Zhao, Jingjing; Li, Yepeng
ABSTRACT: The implications of the CD40-CD40 ligand (CD40L) signaling pathway in systemic lupus erythematosus (SLE) were well documented, due to its important role among immune cells. Previous research found that 3-hydroxy butyrate dehydrogenase 2 (BDH2), a modulator of intracellular iron homeostasis and iron transportation promoted the pathogenic process of SLE by regulating the demethylation of cd70, cd11a, and cd40l genes among CD4 + T cells. The purpose of this study was to explore the role of BDH2 in oxidative damage-induced SLE. First, CD4 + T cells treated with H2 O2 were injected into the tail vein of mice to establish a lupus model. CD40L knockdown significantly decreased CD40L expression on CD4 + T cells in the spleen of SLE mice. Compared with SLE model mice, the levels of serum anti-dsDNA antibody and urinary protein in the CD40L interference group were significantly decreased. CD40L knockdown alleviated the immune complex glomerulonephritis in syngeneic SLE mice. Moreover, the levels of IFN-γ and IL-2 were decreased. However, IL-4 and IL-10 levels were significantly upregulated in the serum of CD40L knockdown SLE mice, compared with SLE model mice. Accordingly, CD40L knockdown reduced Th1/Th2 percentage in SLE mice. Inhibiting the expression of BDH2 of CD4 + T cells promoted the demethylation of CD40L, while it inhibited cell proliferation, elevated oxidative stress through increased expression of CD40L, and thus, promoted the progress of SLE. Our results demonstrate that BDH2 aggravates the pathologic progression of SLE in mice, by increasing the demethylation level of CD40L among CD4 + T cells.